2015
DOI: 10.1007/s00449-015-1487-3
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel production potential of mixed microalgal culture grown in domestic wastewater

Abstract: In this study, a mixed microalgal culture grown in secondarily treated domestic wastewater effluent was investigated for biodiesel production using in situ transesterification method with conventional heating. The total lipid content of the mixed culture was found as 26.2% ± 0.6 by weight of dry biomass, and 74% of the lipids were contributed by total glycerides. In situ transesterification with conventional heating process under acidic conditions produced higher biodiesel yield with chloroform as the co-solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…Methyl esters of palmitic (C16:0), palmitoleic (C16:1), stearic (C18:0), oleic (C18:1) and linolenic (C18:3) acids were the most abundant FAMEs species in the pond biomass lipids (Table 4). The composition was in agreement with what has been reported for wastewater microalgae/biomass lipids (Chinnasamy et al, 2010;Doma et al, 2016;Soydemir et al, 2016;Zhou et al, 2011). The biomass methyl esters during the pond monitoring were dominated by the saturated FAMEs (23-32.2 wt% of the total FAMEs) while the monounsaturated and the polyunsaturated FAMEs ranged 10.8-19.7 wt% and 4.8-10.7 wt% of the total FAMEs, respectively.…”
Section: Wintersupporting
confidence: 87%
See 2 more Smart Citations
“…Methyl esters of palmitic (C16:0), palmitoleic (C16:1), stearic (C18:0), oleic (C18:1) and linolenic (C18:3) acids were the most abundant FAMEs species in the pond biomass lipids (Table 4). The composition was in agreement with what has been reported for wastewater microalgae/biomass lipids (Chinnasamy et al, 2010;Doma et al, 2016;Soydemir et al, 2016;Zhou et al, 2011). The biomass methyl esters during the pond monitoring were dominated by the saturated FAMEs (23-32.2 wt% of the total FAMEs) while the monounsaturated and the polyunsaturated FAMEs ranged 10.8-19.7 wt% and 4.8-10.7 wt% of the total FAMEs, respectively.…”
Section: Wintersupporting
confidence: 87%
“…The values are mean (standard deviations) of two replications during sampling period. quality biodiesel which could meet different standards is 0-1:4-5:0-1 (Ramos et al, 2009;Soydemir et al, 2016). In addition, feedstock lipid profile has a high impact on operational factors and yield of esterification (Knothe, 2005;Marchetti et al, 2007;Ramos et al, 2009).…”
Section: Biomass Lipid Profilementioning
confidence: 99%
See 1 more Smart Citation
“…A good quality biodiesel may be achieved by a mixed culture of selected microalgae, appropriate blending of oils from different monocultivated microalgae or with conventional diesel and the use of polymeric additives. In general, the lipid quality of C. vulgaris UMACC001 cultivated in POME can meet the biodiesel standards and is comparable to previous reports on C. vulgaris (Mallick et al, 2012) and microalgae cultivated in wastewater (Chinnasamy et al, 2010;Soydemir et al, 2016). C. vulgaris UMACC001 had been suggested as a potential strain serving as a biodiesel feedstock based on its fast growth (µ = 0.42 per day) and high SFA content (68.2 wt%) (Vello et al, 2014).…”
Section: Lipid Content and Fatty Acid Profilesupporting
confidence: 87%
“…Recent studies showed that Chlorella is one of the potential microalgae to be used as feedstock for biodiesel production due to its high biomass and lipid productivities and suitable fatty acid composition (Praveenkumar et al, 2014;Vello et al, 2014). Chlorella has been successfully used in bioremediating wastewaters such as rubber industry effluent (Phang et al, 2001), textile discharge (Lim et al, 2010), carpet mill effluent (Chinnasamy et al, 2010), landfill leachate (Mustafa et al, 2012) and domestic wastewater (Soydemir et al, 2016). Culturing Chlorella in wastewaters can reduce the cost of biomass production (Chinnasamy et al, 2010;Soydemir et al, 2016).…”
Section: Introductionmentioning
confidence: 99%